2022
DOI: 10.1007/s11274-022-03425-y
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and antibiofilm activities of bee venom loaded on chitosan nanoparticles: a novel approach for combating fungal human pathogens

Abstract: The prevalence of opportunistic human fungal pathogens is increasing worldwide, and antimicrobial resistance is one of the greatest medical challenges the world faces. Therefore, this study aimed to develop a novel agent to control fungal pathogens. The honeybee products (honey, royal jelly, propolis, bee bread, and bee venom) were screened against unicellular fungal (UCF) pathogens (Cryptococcus neoformans, Kodamaea ohmeri, and Candida albicans) and the bee venom was only exhibited an inhibitory effect agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Figure 2H depicts the mean diameter of particle size distribution. These results were in agreement with those of Taher et al (2017) and El-Didamony et al (2022). It was discovered that the chitosan nanoparticles had a spherical form and that there was a layer around the center of the nanoparticles that included nanoparticles loaded with bee venom.…”
Section: Surface Morphology Using Tem Analysissupporting
confidence: 90%
See 2 more Smart Citations
“…Figure 2H depicts the mean diameter of particle size distribution. These results were in agreement with those of Taher et al (2017) and El-Didamony et al (2022). It was discovered that the chitosan nanoparticles had a spherical form and that there was a layer around the center of the nanoparticles that included nanoparticles loaded with bee venom.…”
Section: Surface Morphology Using Tem Analysissupporting
confidence: 90%
“…This may be due to the antioxidants in Api, which may regulate the generation of reactive oxygen species (ROSs) in fungi, followed by damage to the fungus's lipids, proteins, and DNA; cell death may occur when this balance of components is upset inside the fungal cell (Ratajczak et al, 2021). El-Didamony et al (2022) found that bee venom had a substantial inhibiting impact against C. albicans ATCC 90023, Candida neoformans, and Kodamaea ohmeri, and they The inhibition zone (A) different pathogenic bacteria strains E. faecalis, S. aureus, S. hominis, E. coli, K. pneumonia, and A. baumannii. (B) C. auris and A. niger against by Api, ChB NPs, and Api@ChB NPs.…”
Section: Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bee products such as propolis, bee bread, pollen, honey, royal jelly, or bee venom are regarded as promising sources of antioxidants as they are rich in bioactive compounds such as flavonoids (e.g., kaempferol, quercetin, naringenin) as well as phenolic compounds, including derivatives of cinnamic and benzoic acid [ 27 , 28 , 29 , 30 ]. The therapeutic impact of bee products has been predominantly associated with the plant species and geographic origin of their beehives [ 13 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…For Lyme disease, the melittin present in the venom showed in vitro antibacterial effects against the causative agent Borrelia burgdorferi [ 44 ] and even had significant antibacterial effects against E. coli , S. aureus , and Salmonella typhyimurium [ 45 ]. Melittin also exhibited antibacterial activity against MRSA strains [ 46 ], with antimicrobial potential against agents that cause dental caries, with antifungal capacity including suppression of biofilm formation [ 47 , 48 ]. Its significant antiviral potential has also been demonstrated in in vitro and in vivo assays on different enveloped (Influenza A) and non-enveloped (enterovirus-71) viruses [ 49 ].…”
Section: Introductionmentioning
confidence: 99%